Wave-induced seabed residual response and liquefaction around a mono-pile foundation with various embedded depth. (1st February 2019) - Sui, Titi; Zhang, Chi; Jeng, Dong-sheng; Guo, Yakun; Zheng, Jinhai; Zhang, Wei; Shi, Jian
Abstract: Wave-induced seabed instability caused by the residual liquefaction of seabed may threaten the safety of an offshore foundation. Most previous studies have focused on the structure that sits on the seabed surface (e.g., breakwater and pipeline), a few studies investigate the structure embedded into the seabed (e.g. a mono-pile). In this study, by considering the inertial terms of pore fluid and soil skeleton, a three-dimensional (3D) integrated model for the wave-induced seabed residual response around a mono-pile is developed. The model is validated with five experimental tests available in the literature. The proposed model is then applied to investigate the spatial and temporal pattern of pore pressure accumulation as well as the 3D liquefaction zone around a mono-pile. The numerical simulation shows that the residual pore pressure in front of a pile is larger than that at the rear, and the seabed residual response would be underestimated if the inertial terms of pore fluid and soil skeleton are neglected. The result also shows that the maximum residual liquefaction depth will increase with the increase of the embedded depth of the pile. Highlights: 3D model for wave-induced seabed residual response by considering the inertial terms of pore fluid & soil skeleton. Effects of pile embedded depth on the seabed residual response and liquefaction around the vicinity of mono-pile. Effects of wave reflection and diffraction on seabed residual response with various wave and seabed parameters.